The YouTube effect [videorecording (DVD)] - Winter, Alex, 1965- (Drafthouse Films, 2023)
Director Alex Winter explores the ascension and acceleration of YouTube; a video-sharing website that started with humble origins and has gone on to change how we experience the world. With exclusive access to some of YouTube's biggest stars; the film presents an eye-opening and troubling look at the platform now so powerfully embedded in our lives.